A conserved class of viral RNA structures regulates translation reinitiation through dynamic ribosome interactions - Madeline E. Sherlock; Conner J. Langeberg; Katherine E. Segar; Jeffrey S. Kieft (Cell Reports)
Summary: Certain viral RNAs encode proteins downstream of their main open reading frame, expressed through “termination-reinitiation” events. In some cases, structures located upstream of the first stop codon within these viral RNAs bind the ribosome, inhibiting ribosome recycling and inducing reinitiation. We used bioinformatics methods to identify new examples of viral reinitiation-stimulating RNAs and experimentally verified their secondary structure and function. We determined the structure of a representative viral RNA-ribosome complex using cryoelectron microscopy (cryo-EM). 3D classification and variability analyses reveal that the viral RNA structure can sample a range of conformations while remaining tethered to the ribosome, enabling the ribosome to find a reinitiation start site within a limited range of mRNA sequence. Evaluating the conserved features and constraints of this entire RNA class within the context of the cryo-EM reconstruction provides insight into mechanisms enabling reinitiation, a translation regulation strategy employed by many other viral and eukaryotic systems.